Games in Rigged Economies - Luís F. Seoane (American Physical Society, 2021)
Multiple aspects of an economy can be regulated, tampered with, or left to chance. Economic actors can exploit these degrees of freedom, at a cost, to bend the flow of wealth in their favor. If intervention becomes widespread, microeconomic strategies of different actors can build into emergent macroeconomic effects. How viable is a “rigged” economy? How do growing economic complexity and wealth affect it? We study rigged economies with a toy model. In it, economic degrees of freedom progress from minority to coordination games as intervention increases. Growing economic complexity spontaneously defuses cartels. But excessive complexity leads to large-fluctuations regimes, threatening the system’s stability. Simulations suggest that wealth must grow faster than linearly with economic complexity to avoid this regime and keep economies viable in the long run. We discuss a real-case scenario of multiple economic actors coordinated to result in an emergent upset of the stock market.